2017
DOI: 10.1155/2017/9536148
|View full text |Cite
|
Sign up to set email alerts
|

The Citrus Flavanone Naringenin Protects Myocardial Cells against Age‐Associated Damage

Abstract: In recent years, the health-promoting effects of the citrus flavanone naringenin have been examined. The results have provided evidence for the modulation of some key mechanisms involved in cellular damage by this compound. In particular, naringenin has been revealed to have protective properties such as an antioxidant effect in cardiometabolic disorders. Very recently, beneficial effects of naringenin have been demonstrated in old rats. Because aging has been demonstrated to be directly related to the occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 75 publications
3
38
0
Order By: Relevance
“…ROS, mitochondrial metabolic activity, mitochondrial calcium buffer capacity, and estrogenic signaling functions). Overall the authors suggest that naringenin has antiaging effects on myocardial cells [87].…”
Section: Flavanonesmentioning
confidence: 94%
“…ROS, mitochondrial metabolic activity, mitochondrial calcium buffer capacity, and estrogenic signaling functions). Overall the authors suggest that naringenin has antiaging effects on myocardial cells [87].…”
Section: Flavanonesmentioning
confidence: 94%
“…Orange is a widely available and economically significant fruit containing a large number of polyphenolic secondary metabolites with potent antioxidant and antiproliferative activities [14]. Citrus flavanone naringenin was shown to prevent myocardial cells from senescence through the modulation of cell cycle regulators, ROS levels, and mitochondrial metabolic activities [15]. The juice of bergamot (Citrus bergamia Risso et Poiteau) counteracted the senescence processes in senescent H9c2 cells and old mice [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that NG has several binding sites. NG binding to oestrogen receptors was reported to induce bidirectional adjusting effects, and in another study, to inhibit cell proliferation . Immunosuppressive activity of NG was regulated by its direct interaction with the ligand‐binding site of aryl hydrocarbon receptor .…”
Section: Discussionmentioning
confidence: 94%